Project and technical specifications of the telecontrol system for the Mar del Plata Electrical Distribution System - Pellizzoni, Rodolfo (1993)
This paper describes a project of the Telecontrol System (STC) for the Mar del Plata Electrical Distribution System (SE MDP), which wil provide the automated distribution network management from a Control Center, for both, rural and urban areas. This project will also allow, in the medium term, to incorporate small and medium neighbouring urban centers to this STC. This project was developed taking into account the IEC Standards and Recommendations relating to those topics involved (mainly the IEC-870 series), and represents by itself a new approach to the project and specification of thid type of systems.